ESTIMATE OF TYPES AND QUANTITIES OF BIOMASS IN VOJVODINA - Миладин, Бркић; Тодор, Јанић (Economics of Agriculture, 2011)
The purpose of this paper is to precisely establish the available types and quantities of biomass in Vojvodina, the northern part of Serbia. The analysis was performed based on the changed proprietary relationships, economic transition, and variable technological and technical conditions in agricultural production, forestry, industrial wood processing, and collection of communal refuse. The obtained data were compared with the data collected one, two or three decades ago.The data used in this paper were collected from numerous references: Statistical yearbook of Serbia, papers published in journals, books, monographs, and studies. Biomass quantities were calculated based on following mass ratios: grain/stalks, fruits/cutoff branches, grapes/vine, cattle/manure, tree/wood residue, and number of residents/ communal refuse. Total quantity of produced biomass in Vojvodina equals 10,75 million tons. The total amount of biomass production has dropped for 30 to 40% compared to the last decade. According to estimation based on the previous records of exploitation of biomass in Vojvodina, 30 to 50% of the total amount of biomass can be used for production of energy.